2020
DOI: 10.3389/fmed.2020.570853
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features and Prognostic Assessment of SARS-CoV-2 Infection-Induced Sepsis Among COVID-19 Patients in Shenzhen, China

Abstract: Background: The outbreak of the novel coronavirus disease (COVID-19) that began in December 2019 has posed a great threat to human health and caused a significant loss of life. In Shenzhen, 465 patients were confirmed to have COVID-19 as of August 31, 2020. In the present study, we aimed to describe the clinical characteristics of COVID-19 patients in Shenzhen and identify risk factors for the development of viral sepsis. Methods: In this retrospective study, patients who were confirmed to have a severe acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It has also been found that the most severe cases (including death) of COVID-19 infection indeed all had sepsis 39 . Among COVID-19 patients, septic patients had significantly abnormal immune profile including higher serum IL-6 40 . Many features were similar between bacterial sepsis and SARS-CoV-2 sepsis, although cytokine storm was generally milder in the latter case 41 .…”
Section: Introductionmentioning
confidence: 97%
“…It has also been found that the most severe cases (including death) of COVID-19 infection indeed all had sepsis 39 . Among COVID-19 patients, septic patients had significantly abnormal immune profile including higher serum IL-6 40 . Many features were similar between bacterial sepsis and SARS-CoV-2 sepsis, although cytokine storm was generally milder in the latter case 41 .…”
Section: Introductionmentioning
confidence: 97%
“…Keywords: COVID-19, remdesavir, convalescent plasma, hydroxychloroquine, steroids, MCP, CCL23, programmed death BACKGROUND Individuals infected with severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2; COVID-19) can be asymptomatic or exhibit mild to morbid symptoms depending on viral load and individual characteristics (1)(2)(3)(4)(5). Blood pressure variation, impairments in oxygenation delivery, and metabolomics disruptions are examples of culprits seen in COVID-19 viral septicemia (3,6,7).…”
mentioning
confidence: 99%
“…Activation of protein C occurs in response to vascular injury, increasing the tendency for bleeding [50][51][52]. The cytokine storm potentiates the prevalence of sepsis in COVID-19 patients, especially those who are old and nutritionally deficient [68]. Therefore, the levels of protein S may quickly drop due to SARS-CoV-2-induced septicemia, which is likely to activate procoagulants such as Factor VIII, fibrinogen, and D dimer [66,68].…”
Section: Figurementioning
confidence: 99%
“…The cytokine storm potentiates the prevalence of sepsis in COVID-19 patients, especially those who are old and nutritionally deficient [68]. Therefore, the levels of protein S may quickly drop due to SARS-CoV-2-induced septicemia, which is likely to activate procoagulants such as Factor VIII, fibrinogen, and D dimer [66,68]. Thus, the inflammatory milieu, along with dysregulation in the coagulation cascade, promotes a deadly positive thrombo-inflammatory feedback loop with a concomitant occurrence of thrombosis and hemorrhage in small vessels [6,69].…”
Section: Figurementioning
confidence: 99%